Relation between Pseudoexfoliation Syndrome and Age-Related Cataract - Manar Talaat Mohamed, Ahmed Hassan Aldghaimy, Mohamed Saad Abdelrhman, Ahmed Mostafa Abdelrahman (South Eastern European Journal of Public Health, 2025)
Background: Pseudoexfoliation syndrome (PXF) is a widespread, age-related systemic disease characterized by an atypical deposition of fibrillar extracellular materials. PXF syndrome is closely intertwined with ocular pathologies, particularly with regard to glaucoma and cataract development, and can have a significant impact on both visual function and general wellbeing. Objective: The present study aims to review pathogenesis, clinical features, risk factors, and epidemiologic trends of PXF, with a strong focus placed on its association with age-related glaucoma and cataracts. Methods: A thorough review of current literature was conducted in an attempt to assess the biochemical, genetic, and environmental factors responsible for PXF. In addition, the study covers its ocular complications, its challenging diagnostics, and its therapeutic options. Results: PXF represents a key etiological factor in secondary open-angle glaucoma and increases surgical complications in cases of cataract. Genetic predisposition, oxidative stress, and environmental factors contribute towards its development and progression. PXF varies in prevalence geographically, with a high prevalence in older age groups. Conclusion: Early and continued observation in cases of PXF is important in preventing severe loss of vision. Progress in an understanding of molecular processes involved in PXF could lead to effective therapeutic interventions. Targeted therapeutic interventions and preventive strategies will require additional studies to develop them.